Versatile but Temperamental: A Morphological Study of Palmaris Longus in the Cadaver - Asha Joselet Mathew (Journal of Clinical and Diagnostic Research, 2015)
Introduction: Palmaris longus (PL) is one of the most variable muscles in our body and is vestigial functionally. Its long tendon and its superficial location make it an ideal source for tendon harvesting. Variations such as absence, duplication and reversal have far reaching clinical impact. The aim of this study is to estimate the presence, variants and nerve supply of the PL. Materials and Methods: Upper extremity of 24 cadavers was dissected and PL was examined. The results were compared to other studies on the PL and literature survey was carried out. Results: Thirty nine specimens showed normal morphology and four showed complete agenesis. Other morphological variations seen included - reversed, hybrid, fusiform, fleshy and bifurcated tendon of insertion. Conclusion: Every surgeon must be aware of the variations of the versatile but temperamental PL. Prior knowledge of the layout of the muscle helps in planning intricate surgeries to which this tendon is put use to.